The roots of belonging: childhood predictors of belonging in 22 countries - Victor Counted; Kelly-Ann Allen; Byron R. Johnson; Tyler J. VanderWeele (Scientific Reports)
Abstract Belonging is a fundamental human need, yet its origins in childhood experiences remain underexplored. Childhood predictors of belonging in adulthood using nationally representative data have also largely been overlooked. This study analyzes data from the Global Flourishing Study, a survey of 202,898 individuals from 22 countries, conducted in 2022–2023. Using random effects meta-analyses, the study examines associations between childhood factors and adult belonging. Good relationships with mother and father, and excellent childhood health were positively associated with the outcome, while abuse, feeling like an outsider, and financial difficulties showed substantial negative associations. Immigration status and parental divorce had slight negative impacts, while regular religious attendance was positively associated. Results also reveal considerable country-level variations in effect sizes. In Argentina, a very good relationship with the mother during childhood was a strong positive predictor of adult belonging, while in Japan, the effect was smaller but notable. The effects of childhood abuse on adult belonging are also varied, with a substantial negative effect observed in Turkey and South Africa, compared to a less marked negative effect in the United States and Nigeria. In Spain, Philippines and Brazil, weekly religious service attendance was strongly positively associated with higher belonging in adulthood, whereas in Sweden (and to some extent in South Africa), the effect, though moderate, was negatively associated with belonging. These findings demonstrate the importance of cultural context in shaping the impact of childhood experiences on adult belonging.